Determination of chromium (VI) in primary and secondary fertilizer and their respective precursors. (September 2017) - Krüger, Oliver; Fiedler, Francesca; Adam, Christian; Vogel, Christian; Senz, Rainer
Abstract: Hexavalent chromium species (Cr(VI)) are often carcinogenic, of high acute toxicity, highly mobile, and thus pose a severe risk to health and environment. Fertilizers usually contain significant amounts of chromium. Therefore, a reliable analysis of chromium and the fraction of Cr(VI) are crucial for safe use of fertilizers. This problem is expected to increase in the future, since more and more recycled fertilizers emerge due to increasing fertilizer demand and respective supply risks. However, existing analytical methods have been developed for conventional fertilizers and have to be tested whether they are suitable for the new materials. Thus, we performed a wet-chemical extraction for Cr(VI) on several matrices as well as respective quality control experiments including spiking with Cr(III) and Cr(VI) compounds. We found the Cr(VI) amounts to be below 2 mg/kg except for a thermally post-treated sewage sludge ash (SSA) that showed 12.3 mg/kg. The presence of organic matter e.g. in sludge or precipitated struvite caused a reduction of spiked Cr(VI) and thus no satisfying recovery for quality control. Cr(VI) reduction was also observed for SSA, presumably due to the presence of Fe(II) compounds. Even though the tested procedure can be hampered in some recycled fertilizer matrices, it might be adapted to be applicable also for these complex samples. Graphical abstract: Highlights: Wet-chemical extraction method for Cr (VI) tested on recycling fertilizers. Low Cr (VI) amounts and fractions for most samples (below 2 mgkg −1 ). Method suitable, but might be hampered by organic matter and Fe (II).